22.5k views
4 votes
Given: g(x) = x + 10
Find: g(-12)​

User Sats
by
4.9k points

2 Answers

0 votes

Answer:

g(-12)= -2

Explanation:

We want to find g(x), or y, when x is equal to -12

Therefore, we can substitute -12 in for x

g(x) = x + 10

g(-12)= -12 +10

Add

g(-12)= -2

User McGrady
by
5.5k points
2 votes

Answer:

g(-12) = -2

Explanation:

g(x) = x + 10

Let x = -12

g(-12) = -12+10

g(-12) = -2

User Chrismay
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.